Sentinel lymph node biopsy for oral squamous cell carcinoma. Where are we now?. Issue 8 (October 2017) - Schilling, C.; Shaw, R.; Schache, A.; McMahon, J.; Chegini, S.; Kerawala, C.; McGurk, M.
Abstract: Recent data have confirmed that elective surgical management of the cN0 neck improves survival in patients with early (T1-T2) oral squamous cell carcinoma (SCC), and is better than watchful waiting. However, elective neck dissection (END) may not always be necessary. Sentinel node biopsy (SNB), which is a reliable staging test for patients with early disease and a radiologically N0 neck, can detect occult metastases with a sensitivity of 86%–94%. Patients with no sign of metastases on SNB could avoid neck dissection, and individual treatment should reduce both morbidity and cost. Currently, SNB for oral SCC is available at a limited number of centres in the UK, but this is likely to change as national guidelines have recommended that it is incorporated into the standard treatment pathway. It is therefore important to understand the current evidence that supports its use, its limitations and related controversies, and to plan for a validated training programme.